Profile of the freshman of a municipal school of technical professional education in nursing: product of a professional master's degree (Research, Society and Development, 2020)
This article aims to describe the process of elaborating and applying a socioeconomic form for those entering a technical nursing course with municipal management; and to present the profile of students looking for the technical school, in order to contribute to the curricular planning of this course and others with similar characteristics. This is a qualitative research that used Institutional Analysis as a theoretical-methodological framework, in the Institutional Socioclinical approach. The data were collected through a form, characterized as a product of the dissertation carried out in the professional master's degree in health education to meet a demand from the 16 professors participating in the intervention research. After applying the form to 82 new students, the results revealed that the students are mostly young women, from public education and from families with a considerable percentage of social vulnerability. It is understood that there is an urgent need to expand discussions on the role of the technical school in the training of health professionals, on regional specificities and on the profile of students, creating inclusive and effective educational strategies aimed at this population. It is considered that the role of teachers goes far beyond the classroom and practice scenarios, where they must be attentive to the social, political, economic and cultural context of students looking for the technical course.